Enhancing sports coaching education through a community of practice approach: coach developers' reflections from the coached6 project - Küttel, A.; Senel, E.; Rafnsson, D.; Petrovic, L.; Venzel, N. S.; Storm, L. K.; Kerr-Cumbo, R. (International Sport Coaching Journal, 2026)
Despite the recognized benefits of cross-cultural learning in the globalized world of sports, transnational sports coaching education programs remain scarce and have yet to be widely implemented in Higher Education across Europe. In this practical advance paper, we present how Coach Developers from Malta, Denmark, Iceland, and Turkey, in cooperation with the International Council for Coaching Excellence, collaboratively designed and delivered CoachEd6, a coaching education program at the bachelor`s degree level. Utilizing the six phases of Wenger-Trayner et al.`s community of practice framework, we delve into the identity and dynamics of the group members and the community. We also examine the challenges encountered and how cross-cultural collaboration facilitated overcoming these obstacles, ultimately leading to the successful delivery of the program. We propose that forthcoming cross-national sports coaching programs should view the leading group as a communities of practice and consciously leverage the social dynamics inherent in both developing and delivering coach education to optimize outcomes. This becomes especially critical in the context of Higher Education Institutions within Europe. Moreover, fostering the growth of a communities of practice should be guided by a culturally sensitive leading partner, adopting a flat hierarchy and an ethos of "everyone contributes."